Some Connections between Class 𝒰- and α-Convex Functions - Edmond Aliaga; Nikola Tuneski (Abstract and Applied Analysis)
The class 𝒰(λ,μ) of normalized analytic functions that satisfy |(z/f(z))1+μ·f′(z)−1|<λ for all z in the open unit disk is studied and sufficient conditions for an α-convex function to be in 𝒰(λ,μ) are given.